Spectrum of enterovirus serotypes causing uncomplicated hand, foot, and mouth disease and enteroviral diagnostic yield of different clinical samples - Gao, L; Zou, G; Liao, Q; Zhou, Y; Liu, F; Dai, B; Liu, J; Chen, Z; Xing, W; Yang, L; Liang, H; Zhang, Y; et al. (Oxford University Press, 2018)
Background Hand, foot, and mouth disease (HFMD) represents a substantial disease burden in the Western Pacific region. We investigated the spectrum of causative enteroviruses of HFMD, and evaluated different clinical samples’ diagnostic yield for enteroviruses. Methods We enrolled pediatric patients hospitalized for HFMD among 6 hospitals in Anhua County, Hunan Province, China between October 2013 and September 2016. Throat swabs and stool samples (or rectal swabs) were collected to detect the enterovirus serotypes by real-time reverse-transcription polymerase chain reaction (PCR) or nested PCR. Results Among the 2836 patients, only 1 developed severe illness. Seventeen serotypes were identified in 2401 patients (85%), with the most frequently detected being CV-A16 (29% [814]), CV-A6 (28% [784]), EV-A71 (17% [491]), CV-A10 (4% [114]), and CV-A4 (2% [53]). Children were younger in CV-A6, CV-A10, and CV-A4 infections (median, 12 months; interquartile range [IQR], 12–24 months) than EV-A71 and CV-A16 infections (median, 24 months; IQR, 12–36 months; P < .05). The predominant enterovirus serotype shifted between CV-A16 and CV-A6 during the 3 years. Stool had a higher diagnostic yield (89%) than rectal (77%) and throat swabs (74%). Detection rates reached 93% when testing stools followed by throat swabs if stools were negative, and 89% when testing rectal swabs followed by throat swabs if rectal swabs were negative. Conclusions Our results provide a virological benchmark for future surveillance and diagnostics. Continuous comprehensive virological surveillance is essential, especially after implementation of the EV-A71 vaccine in China, to monitor serotype replacement and the vaccine’s impact.